Investigation of in-beam prompt and delayed neutron counting techniques for detection and characterization of special nuclear material. (March 2021) - Bentoumi, G.; Rogge, R.B.; Ali, F.; Li, L.; Sur, B.
Highlights: In-beam active neutron interrogation developed and deployed at the National Research Universal reactor. MCNPX computational study completed for optimization of the neutron counting system. The neutron counting system permits measurements of prompt and delayed neutrons using a mono-energetic and white thermal neutron beam. The presence of a sub-milligram mass of 235 U could be revealed in less than ten minutes. The technique readily differentiated between 235 U and 233 U isotopes. Detection time reduced to a few seconds in the examination of prompt neutrons. Detection limits of fissile materials were calculated. Abstract: A neutron counting (NC) technique for in-beam active neutron interrogation has been developed and deployed at the National Research Universal (NRU) reactor of the Canadian Nuclear Laboratories (CNL). A distinguishing feature of the method is that the sample to be interrogated remains stationary during the irradiation and counting periods for the detection of prompt and delayed neutrons. The NC system permits measurements of prompt and delayed neutrons using a mono-energetic or broad-spectrum (white) thermal neutron beam. An MCNPX computational study of an NC system employing nine 3 He tubes showed that a delayed neutron detection efficiency of 22% could be achieved. The presence of a sub-milligram mass of 235 U could be revealed in less than ten minutes in the in-beam delayed neutron experiment incorporating a white thermal neutron beam. The technique readily differentiated between 235 U and 233 U isotopes by analysis of delayed neutron count rates. The lower flux of the in-beam DN experiment does not permit the trace analysis that is possible with in-core irradiation, but does permit non-destructive analysis of large samples and could prove invaluable for the initial survey of materials of unknown content and origin. The study also demonstrated that in-beam prompt neutron analysis could be the ultimate solution when the neutron source is weak, the sample is shielded, the fissile mass is small, or interrogation time is limited. Detection time was reduced to a few seconds in the examination of prompt neutrons either in single or coincidence method. This paper presents the application of an in-beam NC system using a mono-energetic and white thermal neutron beam at the NRU reactor and assesses the performance of a newly constructed portable NC system with a large neutron detection array.